Sosialisasi Dampak Gadget Bagi Anak Usia Dini - Lalu Saparwadi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Gadgets have an important role in human life. In addition, the gadget also has a negative impact on its users. This negative impact is caused by use not in accordance with the actual function, especially children. The purpose of this service activity is 1) to provide information about children's cognitive development, 2) to provide information regarding technological developments and their impact on child development, and 3) to provide information on the impact of gadgets on children's development and solutions for dealing with children who are addicted to gadgets. The methods used in this dedication are lectures, discussions, problem solving solutions. This dedication activity was carried out at Plus Muhammadiyah Pancor Elementary School. The results of this dedication show that the participants were enthusiastic and active in discussion activities during the activity.